Polygonatum kingianum polysaccharides ameliorate cognitive impairments in alcohol-exposed obese mice in a sex-specific manner by regulating the gut microbiome and metabolome - Jiayao Lv; Yizhe Qu; Qixin Yan; Ken Cheng; Qingyang Wu; Jiayi Zhang; Xinting Duan; Shanshan Han; Honglei Tian; Lin Shi (Food Research International, 2026)

In situ iron isotopic analysis of mantle silicate minerals by fs-LA–MC–ICP–MS - Xinting Lü; Detao He; Yongsheng Liu; Huajiang Liang; Chunfei Chen; Kexin Deng; Xi Zhu; Ming Li; Yansheng Lai; Ao Yang; Jie Lin; Zhaochu Hu (Chemical Geology, 2026)

Fluvoxamine Attenuates Blood–Brain Barrier Disruption in Drug-Resistance Epilepsy and inhibits Ferroptosis via the Sigma-1 Receptor-TAMM41 signaling in bEnd.3 cells - Lin Guo; Siyu Liu; Na Lv; Jianlun Ji; Xinting Lin; Ying Ke; Zhidong Liu; Congcong Sun; Yun Wang (Molecular Neurobiology, 2026)

Nanozymes design via cost-sensitive machine learning for antibacterial applications - Tianliang Li; Xiao Zhang; Xinting Liu; Lixing Lin; Yuze Ren; Zeyu Li; Yingying Chen; Zhenzhen Li; Lingyan Feng (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

China's marine plastic waste pollution alleviated by the central environmental inspection - Xinting Wang; Pan Yang; Xiaomeng Huan; Lin Yang (Journal of Environmental Management, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

The impact of government subsidies on microplastic pollution control in mariculture: an evolutionary game theory analysis in Qingdao, China - Haiming Song; Xinting Wang; Xiaomeng Huan; Lin Yang (Frontiers in Marine Science, 2025)
Mariculture constitutes the primary origin of microplastic pollution, necessitating immediate action to address microplastic pollution by focusing on both the supply and demand aspects of fishing gear. Based on the cooperative management model of mariculture microplastic pollution, this paper develops an evolutionary game model that incorporates the interactions among fishing gear enterprises, fishermen, and the government. It then proceeds to examine the government’s strategy for managing mariculture microplastic pollution through game theory and simulation analysis. The main findings obtained are as follows. (1) The management of mariculture microplastic pollution can be improved on both the supply chain and market aspects by implementing subsidies. The likelihood of receiving government subsidies boosts the production of environmentally-friendly fishing gear by fishing gear enterprises and the purchase of such gear by fishermen. (2) Based on the cost-benefit variations for fishing gear enterprises, fishermen, and the government, the evolutionary game model reaches distinct equilibrium states, leading to corresponding adjustments in the optimal government subsidy strategy. (3) While there are some positive effects of subsidies, increasing government subsidies does not necessarily lead to better outcomes. As the total amount of subsidies increases, the best practice for governments would be to phase out subsidies for environmentally-friendly fishing gear. Accordingly, the government should build a multi-subject collaborative governance model, reasonably control subsidies amount, prevent the adverse consequences of excessive subsidies, and optimize the structure of subsidy recipients.

In situ Fe isotope analysis of Cr-rich iron oxides using pure chromium metal for isobaric interference corrections by femtosecond LA–MC–ICP–MS - Xinting Lü; Detao He; Yongsheng Liu; Ming Li; Jie Lin; Wei Chen; Lüyun Zhu; Ao Yang; Yantong Feng; Zhenyi Liu; Xianli Zeng; Zhaochu Hu (Chemical Geology, 2024)

Permafrost on the Tibetan Plateau is degrading: Historical and projected trends - Tongqing Shen; Peng Jiang; Qin Ju; Jiahui Zhao; Xuegao Chen; Hui Lin; Bin Yang; Changhai Tan; Ying Zhang; Xinting Fu; Zhongbo Yu (Journal of Hydrology, 2024)

Ketoprofen exposure perturbs nitrogen assimilation and ATP synthesis in rice roots: An integrated metabolome and microbiome analysis - Huan Wang; Zhiheng Li; Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Shaoting Du; Huijun Liu (Environmental Pollution, 2023)

Polystyrene microplastic attenuated the toxic effects of florfenicol on rice (Oryza sativa L.) seedlings in hydroponics: From the perspective of oxidative response, phototoxicity and molecular metabolism - Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Siyi Zhang; Zhiheng Li; Zhiguo Fang; Yuezhong Wen; Huijun Liu (Journal of Hazardous Materials, 2023)

Intelligent feeding control methods in aquaculture with an emphasis on fish: a review - Chao Zhou; Daming Xu; Kai Lin; Chuanheng Sun; Xinting Yang (Reviews in Aquaculture, 2018)
In aquaculture, feeding is the primary factor determining efficiency and cost, so it is important to know when to stop feeding to maximize efficiency. Until now, fish feeding has been mostly based on artificial discrimination, which is usually time‐consuming and laborious. In recent years, intelligent feeding control according to changes in behaviour and growth status has gained increasing attention. This approach involves many methods as well as monitoring and feedback equipment and can automatically determine the feeding demands of fish. This review summarizes the development of intelligent feeding control methods, such as mathematical models, acoustic methods and computer vision, in aquaculture over the past three decades. All methods have unique application scenarios and models for the culture to which they are most suitable, and the advantages and disadvantages of each method in the laboratory as well as in pond, cage and recirculating aquaculture systems are analysed. Studies show that improvements in sensor accuracy and hardware and software processing speed have promoted the development of new technologies and methods, providing effective or potential support for intelligent feeding control. However, its accuracy and intelligent are still need to be improved to meet the needs of actual feeding scenarios. Through close collaborations between engineers and fish behaviourists, the feeding machine and system will be more elaborate and precise on the basis of the above methods, and the level of intelligence will be further improved.